Flipped, refracted, and socratic learning: a triune approach in teaching introduction to philosophy to Indonesian higher students - Dominikus Sukristiono; Ambrosius Lolong Sogen (CV. Literasi Indonesia, 2026)
Teaching Introduction to Philosophy to Indonesian students faces at least these three challenges: first, the challenge of patchiness: students know philosophy patchy and erratic because they are never introduced properly to philosophical thinking; second, the challenge of digital nativity: students are part of Gen Z that are constrained with digital world; third, the challenge of inequal starting points: students come from different background as they are coming from different part of the Indonesian archipelago. To address these challenges, this study demonstrates the effectiveness of integrating three distinct pedagogical approaches simultaneously: Flipped Classroom, Refracted and Socratic Learning. We will show that from the theoretical framework, these approaches are surprisingly connected to each other, and from the experimental study, students perceive these approaches positively. Utilizing a qualitative case study framework backed by diverse data points, this paper explores the experimental application of these approaches and highlights how favorably students perceived the intervention.